Caught in the Crossfire. - Matusow, Barbara (American Journalism Review)
Perhaps no topic elicits so much bitter criticism as coverage of the Middle East. As hard-line supporters of Israel and the Palestinians wage a proxy war via e-mail, threatening phone calls and demonstrations, correspondents and news organizations find themselves the targets of condemnation, often highly personal. Not all news organizations are confronted with organized protests over their Middle East coverage, and those that are do not react uniformly. An informal survey of eight major news outlets turned up a wide variety of responses, from strenuous efforts by National Public Radio (NPR) to mollify its critics to a metaphorical shrug of the shoulders at NBC. NPR provides extensive coverage of the Arab-Israeli conflict and explores Palestinian grievances in more depth than other broadcast outlets. In addition, it is more vulnerable to outside pressure than commercial operations because of its dependence on public largesse. And NPR goes to great lengths to make sure that its Mideast reports are accurate and balanced. But the effort to achieve balance sometimes leads to bleached, uninformative reportage. One problem reporters and editors face is the long-running, repetitive nature of the conflict. INSET: YOU SAY WALL. I SAY FENCE....